On the phylogeny of the late Albian genus Planomalina - M.R. Petrizzo; B. T. Huber (The Journal of Foraminiferal Research, 2006)
The ancestor-descendant relationships of the late Albian Planomalina lineage have been reconstructed using morphologic observations obtained from the Scanning Electron Microscope and supported by morphometric analysis using X-ray images of the shell ontogeny. Both techniques are key to resolving questions on phylogeny and taxonomy, as they allowed us to propose that the trochospiral species Hedbergella wondersi is the ancestor of the genus Planomalina, and to document the Hedbergella wondersi - Globigerinelloides pulchellus - Planomalina praebuxtorfi - Planomalina buxtorfi evolutionary lineage.